(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The importance of studying the comprehensive assessment of the health of applicants-athletes is due to modern problems in the field of physical education and health care. In conditions of intensive training load, stress and irregular physical activity, the problem of maintaining the health of applicants is very relevant. Sport, as an important component of physical culture, can significantly improve the functional state of a person, increase physical fitness and strengthen the immune system. However, to assess the real impact of physical activity on human health, a comprehensive diagnosis is necessary, which includes psychophysical, physiological and social aspects. Assessment of the physical condition of applicants of higher education institutions who are actively involved in sports allows not only to assess the level of their physical fitness, but also to determine the impact of various types of sports activities on the general state of health. Since traditional methods of health assessment cannot always reflect the complete picture, the development of new, comprehensive approaches is necessary for scientifically based monitoring of the health status of applicants. Thus, the analysis of the results indicates that regular physical activity, especially athletics, contributes to improving the level of physical health of applicants. Lack of physical activity or insufficient level of training can lead to a decrease in physical health. Also, comparing the physical condition of applicants who are involved in different sports helps to determine the most effective types of physical activity for maintaining health. For example, the results of the study show that young men who are involved in athletics have better physical health indicators compared to those who do not engage in sports or play volleyball. This may be useful for developing recommendations on physical activity for applicants to higher education institutions.